DESIGN, PRODUCE AND CONTROL OF A 2-DOF UPPER LIMB EXOSKELETAL ROBOT - Yavuz, A.; Akdogan, E.; Aktan, M. E.; Koru, A. T. (YILDIZ TECHNICAL UNIV, 2019)
Exoskeletal robots are used as high-tech products in the military, health and industrial applications. The integration of robots and humans offers new opportunities for the creation of new assistive technologies that can be used in biomedical, industrial and military applications. This paper presents the mechanical design, modeling and simulation of 2 degrees of freedom (DOF) upper limb exoskeletal robot. The system can be used both for supporting load lifting and for rehabilitation of upper limbs. A load cell was used to measure the applied load. Encoders were used to measure the shoulder and elbow joint angles. An electromyograph was developed to measure muscular activation. In this study, simulation was conducted with the PID position control, however the system hardware is applicable for a force control architecture.
Keywords: Exoskeletal robot; EMG; Biomechatronics; REHABILITATION; Thermodynamics